KEABSAHAN PENDAFTARAN TANAH YANG DIAJUKAN OLEH CALON PEMBELI TANAH YANG BELUM BERSERTIPIKAT DI KANTOR PERTANAHAN KABUPATEN PADANG PARIAMAN - syuryani, syuryani; Fajar, Yori Al (JOURNAL OF INDONESIAN COMPARATIVE OF SYARIAH LAW, 2024)
This article explains the validity of land registration submitted by prospective land buyers who have not yet been certified at the Padang Pariaman Regency Land Office which discusses the validity of land registration submitted by prospective land buyers who have not yet been certified at the Padang Pariaman Regency Land Office as well as the obstacles to land registration and their solutions. Land registration is submitted by prospective buyers of land that has not yet been certified at the Padang Pariaman Regency Land Office. To discuss this problem, the author conducted sociological juridical research methods. The results of the research are that there are prospective buyers who submit applications for land registration at the ATR/BPN office of Padang Pariaman district in accordance with the provisions of the UUPA and Government Regulation Number 24 of 1997 and Government Regulation Number 18 of 2021. Obstacles that occur in the land registration process of prospective buyers or applicants If the file is found to be incomplete, it must be completed again to obtain validity. In this writing, it is concluded that on average there are land registration applications submitted by prospective buyers every year, as long as all the requirements are in accordance with the provisions of the law and Circular Letter Number: 500/88/BPN-2007 dated 8 February 2007 concerning Alas Rights: For the purposes of determining rights and land registration in West Sumatra to be fulfilled, the Padang Pariaman Land Office serves for processing. If problems are found, the solution is for prospective land buyers who have not yet been certified to buy land from those who really have the right to avoid land mafia incidents.